Brexanolone (SAGE-547 injection) in post-partum depression: a randomised controlled trial. Issue 10093 (29th July 2017) - Kanes, Stephen; Colquhoun, Helen; Gunduz-Bruce, Handan; Raines, Shane; Arnold, Ryan; Schacterle, Amy; Doherty, James; Epperson, C Neill; Deligiannidis, Kristina M; Riesenberg, Robert; Hoffmann, Ethan; Rubinow, David; et al.
Summary: Background: Post-partum depression is a serious mood disorder in women that might be triggered by peripartum fluctuations in reproductive hormones. This phase 2 study investigated brexanolone (USAN; formerly SAGE-547 injection), an intravenous formulation of allopregnanolone, a positive allosteric modulator of γ-aminobutyric acid (GABAA ) receptors, for the treatment of post-partum depression. Methods: For this double-blind, randomised, placebo-controlled trial, we enrolled self-referred or physician-referred female inpatients (≤6 months post partum) with severe post-partum depression (Hamilton Rating Scale for Depression [HAM-D] total score ≥26) in four hospitals in the USA. Eligible women were randomly assigned (1:1), via a computer-generated randomisation program, to receive either a single, continuous intravenous dose of brexanolone or placebo for 60 h. Patients and investigators were masked to treatment assignments. The primary efficacy endpoint was the change from baseline in the 17-item HAM-D total score at 60 h, assessed in all randomised patients who started infusion of study drug or placebo and who had a completed baseline HAM-D assessment and at least one post-baseline HAM-D assessment. Patients were followed up until day 30. This trial is registered withClinicalTrials.gov, numberNCT02614547 . Findings: This trial was done between Dec 15, 2015 (first enrolment), and May 19, 2016 (final visit of the last enrolled patient). 21 women were randomly assigned to the brexanolone (n=10) and placebo (n=11) groups. At 60 h, mean reduction in HAM-D total score from baseline was 21·0 points (SE 2·9) in the brexanolone group compared with 8·8 points (SE 2·8) in the placebo group (difference −12·2, 95% CI −20·77 to −3·67; p=0·0075; effect size 1·2). No deaths, serious adverse events, or discontinuations because of adverse events were reported in either group. Four of ten patients in the brexanolone group had adverse events compared with eight of 11 in the placebo group. The most frequently reported adverse events in the brexanolone group were dizziness (two patients in the brexanolone group vs three patients in the placebo group) and somnolence (two vs none). Moderate treatment-emergent adverse events were reported in two patients in the brexanolone group (sinus tachycardia, n=1; somnolence, n=1) and in two patients in the placebo group (infusion site pain, n=1; tension headache, n=1); one patient in the placebo group had a severe treatment-emergent adverse event (insomnia). Interpretation: In women with severe post-partum depression, infusion of brexanolone resulted in a significant and clinically meaningful reduction in HAM-D total score, compared with placebo. Our results support the rationale for targeting synaptic and extrasynaptic GABAA receptors in the development of therapies for patients with post-partum depression. A pivotal clinical programme for the investigation of brexanolone in patients with post-partum depression is in progress. Funding: Sage Therapeutics, Inc.